Critical Analysis and Reformulation of the Qibla Deviation Formula in the Book of Mekanika Benda Langit - Luthfi, Muhammad; Fajri, M. Nur Iskandar; Reza, Izam Bahtiar; Aziz, M Abdul (Al-Hilal: Journal of Islamic Astronomy, 2025)
The calculation of Qibla deviation using the formula presented in the Mekanika Benda Langit book has become widely adopted and frequently cited in academic studies. However, this method still produces noticeable inaccuracies. This research aims to identify the causes of error in the Qibla deviation formula described in the Mekanika Benda Langit book and to reformulate a more accurate method for determining the Qibla direction. The study employed a literature-based qualitative design, with data obtained through documentation and interviews. Data analysis was conducted using descriptive statistical methods within a multidisciplinary approach. The findings reveal that the inaccuracy arises from the formula's reliance on the ratio between an arc and a flat circle, making it valid only for short distances (up to 2,000 km). A reformulation using spherical trigonometry provides higher precision and consistency across all distances and longitudinal variations. This new formulation significantly improves the accuracy of Qibla deviation calculations compared to the original method in Mekanika Benda Langit book.